Herb-partitioned moxibustion alleviates colonic inflammation in Crohn's disease rats by inhibiting hyperactivation of the NLRP3 inflammasome via regulation of the P2X7R-Pannexin-1 signaling pathway. - Ji Zhang (Public Library of Science (PLoS), 2021)
Crohn's disease is a chronic inflammatory bowel disease and the NLRP3 inflammasome plays an important role in Crohn's disease. Previous studies have shown that Herb-partitioned moxibustion treating (at Qihai (CV 6) and Tianshu (ST 25)) prevented the excessive activation of the NLRP3 inflammasome and repaired damaged colonic mucosa in Crohn's disease. However, the mechanism by which Herb-partitioned moxibustion (at CV 6 and ST 25) regulates NLRP3 remains unclear. In this study, we treated Crohn's disease rats with herb-partitioned moxibustion (at CV 6 and ST 25) to investigate the mechanism by which Herb-partitioned moxibustion regulates the colonic NLRP3 inflammasome by observing colon length, the colon macroscopic damage indexes, and the expression of ATP, P2X7R, Pannexin-1, NF-κBp65, NLRP3, ASC, caspase-1, IL-1β and IL-18 in the colon in Crohn's disease. Here, this study shows that herb-partitioned moxibustion (at CV 6 and ST 25) can reduce colon macroscopic damage indexes and colon histopathological scores, alleviate colon shortening and block the abnormal activation of the NLRP3 inflammasome by inhibiting the ATP content and the expression of P2X7R, Pannexin-1 and NF-κBp65, thereby reducing the release of the downstream inflammatory cytokine IL-1β and ultimately suppressing colonic inflammation in Crohn's disease rats. This study for the first time identifies the mechanism by which herb-partitioned moxibustion (at CV 6 and ST 25) may inhibit the abnormal activation of the NLRP3 inflammasome by inhibiting the P2X7R-Pannexin-1 signaling pathway in Crohn's disease rats.